A pharmacogenomic assessment of psychiatric adverse drug reactions to levetiracetam. Issue 6 (1st April 2022) - Campbell, Ciarán; McCormack, Mark; Patel, Sonn; Stapleton, Caragh; Bobbili, Dheeraj; Krause, Roland; Depondt, Chantal; Sills, Graeme J.; Koeleman, Bobby P.; Striano, Pasquale; Zara, Federico; Sander, Josemir W.; et al.
Abstract: Objective: Levetiracetam (LEV) is an effective antiseizure medicine, but 10%–20% of people treated with LEV report psychiatric side‐effects, and up to 1% may have psychotic episodes. Pharmacogenomic predictors of these adverse drug reactions (ADRs) have yet to be identified. We sought to determine the contribution of both common and rare genetic variation to psychiatric and behavioral ADRs associated with LEV. Methods: This case‐control study compared cases of LEV‐associated behavioral disorder ( n  = 149) or psychotic reaction ( n  = 37) to LEV‐exposed people with no history of psychiatric ADRs ( n  = 920). All samples were of European ancestry. We performed genome‐wide association study (GWAS) analysis comparing those with LEV ADRs to controls. We estimated the polygenic risk scores (PRS) for schizophrenia and compared cases with LEV‐associated psychotic reaction to controls. Rare variant burden analysis was performed using exome sequence data of cases with psychotic reactions ( n  = 18) and controls ( n  = 122). Results: Univariate GWAS found no significant associations with either LEV‐associated behavioural disorder or LEV‐psychotic reaction. PRS analysis showed that cases of LEV‐associated psychotic reaction had an increased PRS for schizophrenia relative to contr ols ( p  = .0097, estimate = .4886). The rare‐variant analysis found no evidence of an increased burden of rare genetic variants in people who had experienced LEV‐associated psychotic reaction relative to controls. Significance: The polygenic burden for schizophrenia is a risk factor for LEV‐associated psychotic reaction. To assess the clinical utility of PRS as a predictor, it should be tested in an independent and ideally prospective cohort. Larger sample sizes are required for the identification of significant univariate common genetic signals or rare genetic signals associated with psychiatric LEV ADRs.